2012
DOI: 10.1093/ntr/nts134
|View full text |Cite
|
Sign up to set email alerts
|

Does Tobacco-Control Mass Media Campaign Exposure Prevent Relapse Among Recent Quitters?

Abstract: Objective: To determine whether greater mass media campaign exposure may assist recent quitters to avoid relapse.Method: Using date of data collection and postcode, media market estimates of televised tobacco-control advertising exposure measured by gross ratings points (GRPs) were merged with a replenished cohort study of 443 Australians who had quit in the past year. Participants' demographic and smoking characteristics prior to quitting, and advertising exposure in the period after quitting, were used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
(32 reference statements)
1
25
1
Order By: Relevance
“…Since recent quitters are likely to relapse,6 28 it is important to enhance both promotion of cessation and prevention of relapse. We confirmed that tobacco price rises were significantly associated with increasing cessation among smokers and decreasing relapse among quitters concurrently 1.…”
Section: Resultsmentioning
confidence: 99%
“…Since recent quitters are likely to relapse,6 28 it is important to enhance both promotion of cessation and prevention of relapse. We confirmed that tobacco price rises were significantly associated with increasing cessation among smokers and decreasing relapse among quitters concurrently 1.…”
Section: Resultsmentioning
confidence: 99%
“…This may indicate that aside from being recalled more often, graphic and emotional advertisements with personal narratives may be able to reach a larger portion of the smoking population than other forms of advertisements. Others have found recently that this type of advertisement has tested well even in developing countries and among indigenous people groups (14,18,53).…”
Section: Discussionmentioning
confidence: 95%
“…The majority of evidence indicates that these mass media campaigns are effective in motivating individuals to think about quitting, try to quit, get help for quitting and stay quit (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). At the population level, advertisements are also associated with decreases in cigarette consumption and smoking prevalence (13,15,16,19,(30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…Recall of mass media advertising has been shown to increase with broadcast intensity, 23 25 which is fundamental to achieving good reach among smokers of low socioeconomic status 6 , 25 . ‐ 27 Broadcast intensity is also important for influencing quitting activity and success 5 , 6 , 22 , 25 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%